Analisis Semiotika pada Film Damsel Menurut Teori Charles Sanders Pierce - Deniela Yoshelyn S.; Efani Margareth G.; Grace Fanesya G.; Nurul Nabila L.; Salsabil Putri; Tri Indah Prasasti (Departement of Mathematics Education, 2024)
This article discusses the analysis of semiotic theory according to Charles Sanders Pierce contained in the film